Rupture épistémologique et travail sur les représentations - Michel Fabre (Recherches en Éducation)
In this paper, we try to answer the question of changing conceptions from Gaston Bachelard’s point of view. From the example of teaching Kepler’s laws, it describes the cathartic strategies of the psychoanalysis of the knowledge. Changing conception means awareness (topical dimension), investments (energetic dimension), and intellectual supervision (dynamic dimension). Bachelard so defines a dialectic of continuity and break (and not cut) in which psychology is working to free the reason from epistemologic obstacles which hinder it. From this point of view, changing conceptions is thought as problématization, that is to take away from opinion to a rational knowledge.